2018
DOI: 10.1101/478396
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Polymorphic 30-nm Chromatin Fiber and Linking Number Paradox. Evidence for the Occurrence of Two Distinct Topoisomers

Abstract: We discuss various models of spatial organization of the 30-nm fiber that remains enigmatic despite 40 years of intensive studies. Using computer simulations, we found two topologically different families of the fiber conformations distinguished by the linker length, L: the fibers with L = {10n} and {10n+5} bp have DNA linking numbers per nucleosome DLk » -1.5 and -1.0, respectively. The fibers with DLk » -1.5 were observed earlier, while the topoisomer with DLk » -1.0 is novel. These predictions were confirme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 58 publications
(138 reference statements)
3
2
0
Order By: Relevance
“…2 C ). Overall, the FLD profile calculated for a mixture of T1 and T2 topoisomers ( 78 ) is in qualitative agreement with the experimental data ( Fig. 3 , A – C ).…”
Section: Introductionsupporting
confidence: 85%
See 1 more Smart Citation
“…2 C ). Overall, the FLD profile calculated for a mixture of T1 and T2 topoisomers ( 78 ) is in qualitative agreement with the experimental data ( Fig. 3 , A – C ).…”
Section: Introductionsupporting
confidence: 85%
“…It is therefore unlikely that RICC-seq data can be interpreted based solely on the crystal structures of chromatin fibers, and some alternative fiber conformations should be taken into account. We suggested that the novel T1 topoisomer described above could be such an alternative ( 78 ).
Figure 3 Comparison of the experimental RICC-seq data with theoretical predictions.
…”
Section: Introductionmentioning
confidence: 99%
“…We suggest that topological polymorphism of chromatin fibers may play a role in the process of transcription, i. e., the {10n þ 5} DNA linkers are likely to produce transcriptionally competent chromatin structures. This hypothesis is consistent with available data for several eukaryotes, from yeast to mouse (Norouzi, Katebi, Cui, & Zhurkin, 2015;Norouzi and Zhurkin, 2018). Here, we analyzed the data from a recent genome-wide radio-probing study of DNA folding in human cells.…”
Section: Ran Sun Zilong LI and Thomas C Bishopsupporting
confidence: 86%
“…We show that the novel topoisomer with Lk % -1.0 has to be taken into account to interpret the experimental data, especially for the transcriptionally active regions (Figure 1). This is yet another evidence for occurrence of two distinct fiber topoisomers (Norouzi and Zhurkin, 2018). Potentially, our findings may reflect a general tendency of chromosomal domains with different levels of transcription to retain topologically distinct higherorder fiber conformations, T1 and T2.…”
Section: Ran Sun Zilong LI and Thomas C Bishopsupporting
confidence: 58%
See 1 more Smart Citation